The Impact of Price, Service Quality, and Store Atmosphere on Customer Loyalty: A Starbucks Reserve Study - Simatupang, Monika; Pasaribu, Lamhot Henry (Indonesian Scientific Publication, 2025)
This study analyzes the influence of Price Perception, Service Quality, and Store Atmosphere on Customer Satisfaction and Customer Loyalty at Starbucks Reserve Plaza Senayan Jakarta. This study applied a quantitative research design, and the data were collected through structured questionnaires to 290 respondents. This study employed Structural Equation Modeling- Partial Least Squares (SEM-PLS) to test hypotheses empirically. Empirical findings confirm that Service Quality and Price Perception positively and significantly affect Customer Satisfaction, a key driver of Customer Loyalty. Store Atmosphere directly improves customer satisfaction, though with an uncertain statistical correlation with Customer Loyalty. These results emphasize pricing and service differentiation as the most critical factors in keeping a customer, particularly for the rival coffee shop market. This study contributes to the literature by offering implications of consumer behavior in the luxury coffee shop market and supplying managerial recommendations for Starbucks and other luxury coffee brands. The results suggest that firms should focus on value-based pricing and services to promote customer loyalty. The study also indicates the need to conduct further research on the indirect effect of store atmosphere on customer engagement in the long term.